Social network type contributes to purpose in life among older people, mediated by social support. - Bakhshandeh Bavarsad M; Stephens C (Springer Nature, 2024)
A sense of Purpose in Life is an important aspect of ageing well which is related to older adult's social relationships. Social network types and the different sources of support they provide are theorized here as a pathway to maintaining a sense of purpose as we age. The study utilized a population sample from the 2016 and 2020 NZ Health, Work, and Retirement (NZHWR) longitudinal survey waves; N = 2869 (mean age of 65.82 years (SD = 6.40). A structural equation model investigated the relationship between Social Network Type and Purpose in Life and the mediating role of Social Support. The final model had a good fit to the data and explained 33.7% of the variance in Purpose in Life. Private, Self-Contained and Family Dependent network types (2016) were negatively related to Purpose in Life 4 years later (2020). Support from sense of Attachment, Reassurance of Worth, Reliable Alliance and Social Integration played a mediating role between Social Network type and Purpose in Life. These findings highlight the importance of social networks in maintaining a sense of purpose among older adults and highlight pathways for the types of networks, and kinds of social support they offer, which contribute to a sense of purpose in life. They underscore the importance of social support for the well-being of older adults and highlight the need to consider the quality and type of social networks and support they provide, when designing interventions to enhance well-being.
Keywords: Quality of life; Structural equation models; Successful ageing